2020
DOI: 10.1186/s12943-020-01235-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circPACRGL promotes progression of colorectal cancer via the miR-142-3p/miR-506-3p- TGF-β1 axis

Abstract: Background Colorectal cancer (CRC) is the leading cause of cancer-related death worldwide. Exosome shave emerged as crucial regulators of intercellular communication and that abundant Circular RNAs (circRNAs) are enriched within exosomes. CircRNAs are novel members of noncoding RNAs regulating cancer proliferation and progression. However, the function and regulatory mechanism of cancer-derived exosomal circRNAs in CRC remains unclear. Methods CRC cells-derived exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
210
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(235 citation statements)
references
References 27 publications
2
210
0
Order By: Relevance
“…CircPACRGL promoted the proliferation, migration and invasion of CRC cells and the differentiation of Neutrophils from N1 to N2 via miR-142-3p/miR-506-3P-TGF-1 axis. This study is the first to reveal the role of cancer-derived exosomal circPACRGL in CRC proliferation and metastasis (Shang et al, 2020).…”
Section: Exosomal Circrnas May Be Therapeutic Targets For Inhibitingmentioning
confidence: 84%
“…CircPACRGL promoted the proliferation, migration and invasion of CRC cells and the differentiation of Neutrophils from N1 to N2 via miR-142-3p/miR-506-3P-TGF-1 axis. This study is the first to reveal the role of cancer-derived exosomal circPACRGL in CRC proliferation and metastasis (Shang et al, 2020).…”
Section: Exosomal Circrnas May Be Therapeutic Targets For Inhibitingmentioning
confidence: 84%
“…For instance, exosomal circPACRGL contributed to the progression of CRC by regulating miR-142-3p/miR-506-3p-TGF-β1 axis. 41 Exosome-delivered hsa_circ_0005963 facilitated glycolysis to induced chemoresistance by the miR-122/PKM2 axis in CRC. 42 A previous report showed that circ_IFT80 expression was upregulated in CRC serum exosomes, CRC tissues and CRC cells, circ_IFT80 silencing repressed cell proliferation while accelerated apoptosis through miR-1236-3p/HOXB7 axis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“… 23 And Shang et al proposed that miR-142-3p also participated in the positive regulation of exosomal circPACRGL on colorectal cancer progression. 24 In addition, miR-142-3p had been found to have regulatory effects on chemotherapy sensitivity and cell autophagy in breast cancer. 25 In NSCLC, the previous studies revealed that miR-142-3p could hinder cancer progression and promote cancer chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%